ANALISIS RELEVANSI DAN DAMPAK PELAKSANAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY TERHADAP MASYARAKAT SEKITAR: Studi kasus PT Surya Sakti Darma Kencana, Kalimantan Selatan - Putri Puspita Rini; Diane Frisko (CALYPTRA, 2015)
This research is dedicated to learn how a CSR program is being conducted and what is the effect given by the company and flash back from the surrounding society as a long-term investment for the company. This research is using quantitative approach with descriptive research method. The purpose of this research is to know how a CSR program being conducted and what is the impact of the surrounding society. The research is conducted to PT Surya Sakti Darma Kencana in Kalsel on 18 july 2013 to 20 jan 2014. In this research it can be concluded that the whole planned program is being executed. However, in the execution there are weaknesses that the relt of the program is not maximal. From the weaknesses the recommended solution is there should be participation from the recipient of the program included in the planning as well as execution, there should be mensurement and clear report so that information obtained could be used as evaluation for the next program.